Proactive Medico-Psychological Assistance for Patients with Chronic Pain: A Clinical Study of Effectiveness - Khaustova, Олена; Грачова, Ангеліна (Psychosomatic Medicine and General Practice, 2025)
Relevance. Chronic pain is one of the most widespread and complex medical and social problems of modern healthcare: according to estimates, it affects up to 20% of the adult population [1]. Comorbid mental disorders, particularly anxiety and depression, are diagnosed in approximately 40% of such patients [3]. Under wartime conditions, this problem is aggravated: traumatic injuries cause persistent pain syndrome in the vast majority of wounded individuals—up to 83% [4], often accompanied by post-traumatic and anxiety disorders. Pain and emotional distress form a pathological vicious cycle: nociceptive input activates the stress response and brain structures associated with fear [5], while anxiety contributes to pain catastrophizing and avoidance behavior [6]. This mutual reinforcement worsens prognosis and hinders rehabilitation. Timely detection and correction of psychological factors is a critical component of modern pain medicine [7]. The biopsychosocial model of pain emphasizes the need for a complex, interdisciplinary approach [7], and proactive strategies aimed at early intervention may potentially disrupt the “pain–anxiety” cycle. However, in Ukrainian clinical practice, a predominantly medicalized approach with reliance on pharmacotherapy still prevails, limiting the effectiveness of rehabilitation and increasing the burden of repeated visits, escalating medication dosages, and social maladaptation [8]. The relevance of the proactive approach to chronic pain has been repeatedly emphasized in Ukrainian literature. For example, Professor O.S. Chaban and Professor O.O. Khaustova highlight the importance of timely identification of psycho-emotional disorders in patients with somatic complaints and chronic pain, advocating for the use of standardized psychodiagnostic tools [23]. The study by A.I. Kohut and O.S. Chaban [24] demonstrated the effectiveness of using PCL-5, GAD-7, and PHQ-9 in identifying symptoms of post-traumatic and anxiety-depressive disorders in the context of combat trauma. Also, the work of I.V. Chernenko and M.I. Markova [25] described the relationship between psychosocial maladjustment and the severity of post-traumatic burden in veterans—aligning with the concept of multidimensional distress in chronic pain. These publications provide a solid methodological foundation for implementing psychocorrectional programs in rehabilitation institutions. Therefore, the introduction of accessible, standardized, and evidence-based proactive psychological interventions appears not only desirable but essential in improving the quality of life for patients with chronic pain in wartime settings. Objective. To assess the role of anxiety disorders in the clinical presentation of chronic pain syndrome and evaluate the effectiveness of a proactive psychomedical intervention in reducing anxiety and improving patient adaptation during post-traumatic rehabilitation. Methods: The study involved 32 male patients aged 23 to 70 years (M = 34.9; SD = 5.7) undergoing inpatient rehabilitation after combat-related limb injuries. A prospective one-factor pre-post intervention design was used. Psychological assessment included standardized tools: GAD-7 (generalized anxiety), PHQ-9 (depression), SSS-8 (somatic symptoms), SPAASMS (pain adaptation), and the 4DSQ (Four-Dimensional Symptom Questionnaire). The 6-week intervention included psychoeducational modules, cognitive-behavioral techniques, and self-regulation skills training. Paired t-tests and Pearson correlation were used for statistical analysis. Results. At baseline, most patients had clinically significant levels of anxiety, depression, and somatization. The mean GAD-7 score was 13.97±2.12, PHQ-9 — 16.76±3.47, and SSS-8 — 11.52±2.81. After the intervention: Anxiety (GAD-7) decreased to 7.08 (–49%; p<0.001), Depression (PHQ-9) to 7.81 (–53%; p<0.001), Somatization (SSS-8) to 6.12 (–47%; p<0.001), Subjective distress (4DSQ) to 13.87 (–34%; p<0.001). The proportion of patients with high anxiety (GAD-7 ≥15) dropped from 21.9% to 3.1%, and with severe depression (PHQ-9 ≥20) from 28.1% to 0%. Significant correlations were observed between GAD-7 and pain adaptation (SPAASMS), with r = 0.46 (p<0.01), confirming the emotional contribution to pain perception. Conclusions. The proactive psychological program integrated into rehabilitation treatment proved highly effective in reducing anxiety, depression, and somatic complaints in patients with trauma-related chronic pain. Early identification and targeted correction of anxiety contributed to breaking the “pain–anxiety” cycle, improving emotional well-being, pain tolerance, and overall adaptation. These findings support the inclusion of proactive psychomedical interventions in rehabilitation care standards. Given the growing mental health burden from war-related trauma, such approaches are not only clinically, but also socially meaningful, aiding recovery and reintegration into everyday life.